Animal spirits how human psychology drives the economy, and why it matters for global capitalism - Akerlof, George A. 1940-; Shiller, Robert J. (Princeton University Press, 2010)
The global financial crisis has made it painfully clear that powerful psychological forces are imperiling the wealth of nations today. From blind faith in ever rising housing prices to plummeting confidence in capital markets, "animal spirits" are driving financial events worldwide. In this book, the authors, both economists, challenge the economic wisdom that got us into this mess, and put forward a bold new vision that will transform economics and restore prosperity. They reassert the necessity of an active government role in economic policymaking by recovering the idea of "animal spirits", a term John Maynard Keynes used to describe the gloom and despondence that led to the Great Depression and the changing psychology that accompanied recovery. Like Keynes, they know that managing these animal spirits requires the steady hand of government; simply allowing markets to work won't do it. In rebuilding the case for a more robust, behaviorally informed Keynesianism, they detail the most pervasive effects of animal spirits (i.e. human psychology), in contemporary economic life, such as confidence, fear, bad faith, corruption, a concern for fairness, and the stories we tell ourselves about our economic fortune, and show how Reaganomics, Thatcherism, and the rational expectations revolution failed to account for them. The authors then offer a road map for reversing the financial misfortunes besetting us today; they teach how leaders can channel animal spirits, the powerful forces of human psychology that are afoot in the world economy today, and making them work for and not against us.